Cicero, Against Verres, 2.1.53-86 : Latin text with introduction, study questions, commentary and English translation - Cicero, Marcus Tullius (Classics textbooks ;, 2011)
This volume provides a portion of the original text of Cicero's speech in Latin, a detailed commentary, study aids and a translation. Ingo Gildenhard's commentary will be of particular interest to students of Latin at both high school and undergraduate level. It will also be of help to Latin teachers and to anyone interested in Cicero, language and rhetoric, and the legal culture of Ancient Rome.